A companion to twelfth-century schools
1 online resource.
Keywords: This Companion to Twelfth-Century Schools provides a comprehensive update and new synthesis of the last three decades of research. The fruit of a contemporary renewal of cultural history among international scholars of medieval studies, this collection draws on the discovery of new texts, the progress made in critical attribution, the growing attention given to the conditions surrounding the oral and written dissemination of works, the use of the notion of a “community of learning”, the reinterpretation of the relations between the cloister and the urban school, and links between institutional history and social history. Contributors are: Alexander Andrée, Irene Caiazzo, Cédric Giraud, Frédéric Goubier, Danielle Jacquart, Thierry Kouamé, Constant J. Mews, Ken Pennington, Dominique Poirel, Irène Rosier-Catach, Sita Steckel, Jacques Verger, and Olga Weijers.